BK virus: Current understanding of pathogenicity and clinical disease in transplantation. (8th April 2019) - Chong, Stephanie; Antoni, Michelle; Macdonald, Andrew; Reeves, Matthew; Harber, Mark; Magee, Ciara N.
Summary: BK polyomavirus (BKV) is an important cause of graft loss in renal transplant recipients that continues to pose a significant challenge to clinicians due to its frequently unpredictable onset, persistence, and the lack of effective antiviral agents or prevention strategies. This review covers our current understanding of epidemiology, viral transmission and disease progression, and treatment and prevention strategies that have been used to manage this disease.